Dahschur, Ägypten: Die Arbeiten der Jahre 2014 und 2015 - Alexanian, Nicole; Arnold, Felix; Herbich, Tomasz; Müller, Sandra (e-Forschungsberichte des DAI, 2023)
The necropolis of Dahshur is characterised by the building projects of King Snofru (about 2600 BC). He created a ritual landscape by altering considerable parts of the natural landscape and by building two giant pyramids – the Red Pyramid and the Bent Pyramid – several temples, cemeteries and settlements. In 2014 the magnetometric survey to the north and to the south of the valley temple of the Bent Pyramid was continued. Furthermore a so far unknown and unique element of landscape architecture was identified. Directly to the north of the valley temple of the Bent Pyramid a large garden which was enclosed by a massive mudbrick wall could be recorded. In spring 2015 magnetic surveys were undertaken in the area of the workmen’s barracks in the vicinity of the Red Pyramid and the area of the so-called valley temple of the Bent Pyramid. Drill sondages in the valley to the east of the Bent Pyramid confirmed the existence of an eastern harbor wall. Drill sondages showed furthermore that a transport way of limestone blocks, which was used in the New Kingdom when the valley temple was dismantled, continues down the whole wadi. Like in the years before, several new relief fragments from the valley temple were discovered within this limestone way. The excavation of a miniature mastaba to the north-west of the pyramid of Amenemhat II revealed a burial with a broad collar from faience beads. The tomb dates to the late Old Kingdom or First Intermediate Period.